Diabetes education in Oman: needs assessment and development of an intervention for health care professionals - Al-Subhi, Lyutha Khalfan, author; Kendall, Patricia, advisor; Adams, Elizabeth, advisor (Colorado State University. Libraries, 2007)
Oman is one of the countries faced with the challenge of an increasing rate of diabetes. The National Diabetes Control Program (NDCP), in Oman, aims to provide a suitable and quality health education to people with diabetes and the community. Diabetes management guidelines for Primary Health Care (PHC) in Oman point out that all members of the diabetes health care team share the responsibility of educating those with diabetes. Nevertheless, diabetes education has not been tackled systematically and the incidence of diabetes is on the rise in Oman. There is a pressing need for a diabetes education program for diabetes self management in the Sultanate of Oman.

In the first phase, an educational needs assessment was conducted with people with Type 2 diabetes in PHC. Structured open-ended one-on-one interviews were employed, based on the tenants of the Health Belief Model (HBM), to better understand patients’ beliefs, motivators, and barriers associated with their diabetes self-management behaviors. Health professionals were also interviewed to identify their perspectives and suggestions on the diabetes education needs in PHC. Patient interviews identified four major barriers to appropriate self-care behaviors among people with Type 2 diabetes, inadequate knowledge, lack of self-efficacy, social commitments, and limited finances. No diabetes education program was found to be in place in PHC. Professionals and patients expressed the need for educational materials that were pragmatic and culturally appropriate.

In the second phase of the study a comprehensive culturally appropriate diabetes education program and related printed materials were developed. The program was pilot tested with a group of health professionals from PHC in a quasi-experimental design. A closed ended questionnaire was used to evaluate the effectiveness of the program in equipping professionals with appropriate diabetes education knowledge and skills important in counseling patients. The program was also evaluated by the treatment group using an open-ended questionnaire. Knowledge of the treatment group increased significantly (p < 0.0001) from pre-test to post-test evaluation on all knowledge scales; it was retained at one-month follow-up. Self-efficacy was significantly (p = 0.006) increased at post-test in the treatment group and was maintained at follow-up. The comparison group did not show any change in knowledge or attitude scale at any testing point. Treatment participants provided positive feedback on the usefulness of the program. The diabetes education program should be piloted with a group of patients and evaluated before it is fully implemented in Oman.
Keywords: diabetes education; health care professionals; needs assessment; health education; public health; diabetes; studies